A comparative study on the structural and functional properties of water‐soluble and alkali‐soluble dietary fibres from rice bran after hot‐water, ultrasound, hydrolysis by cellulase, and combined pre‐treatments. (6th December 2021) - Zadeike, Daiva; Vaitkeviciene, Ruta; Degutyte, Rimgaile; Bendoraitiene, Joana; Rukuiziene, Zaneta; Cernauskas, Darius; Svazas, Mantas; Juodeikiene, Grazina
Summary: The aim of the study was to estimate the optimum method to obtain water‐soluble (WS‐DF) and alkali‐soluble (AS‐DF) dietary fibres fibres from defatted rice bran (DRB) to develop functional components for food. The different pre‐treatments of DRB, such as ultrasound (US) treatment, hydrolysis by cellulase (HC) and combined treatment (HC‐US), were compared with hot‐water (HWT) treatment on yields, and structural, physicochemical, and functional properties of WS‐DF and AS‐DF. Results showed that amounts of WS‐DF (5.54–9.03 g/100 g) and AS‐DF (7.22–9.58 g/100 g), and total dietary fibre (TDF) (42.21–45.44 g/100 g) obtained from the DRB after US, HC and HC‐US treatments were significantly higher than that after HWT (6.36, 5.65 and 31.92 g/100 g, respectively). The FT‐IR indicated that the effect of applied treatments on the changes of the chemical structure of polysaccharides was stronger for the WS‐DF than that for the AS‐DF. Scanning electron microscopy (SEM) showed that the surfaces of US‐treated DFs particles were much more fractured than those after the HWT and HC. The combined HC‐US treatment at 50°C for 30 min significantly enhanced the purity (85–91%) and homogeneity of RB DFs structure resulting in increased water‐holding, swelling and glucose adsorption capacities compared to conventional processes maintaining acceptable bioactivity. Our study showed that conventional hot water extraction could be replaced with the ultrasonication technology as an effective tool for the modification of rice bran DFs' structure and functional properties. Abstract : Novel strategy to modify the microstructure of rice bran dietary fiber while improving functional properties and maintaining biological activity.